Factors influencing antenatal mothers' choice of hospital for delivery at Hospiatl Universiti Sains Malaysia (HUSM) and Hospital Kota Bharu(HKB) - Sulaiman, Zaharah; Hassan, Mohd Hashim Mohd; Mohd Hashim Mohd, Mazlan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
The selection of a hospital for delivery does not become an issue for women until they become pregnant. The main aim for promoting hospital delivery is to ensure safety to the mother and the newborn child. The main objective in this study is to determine the factors that influence antenatal mothers choice of hospitals for delivery at Hospital Universiti Sains Malaysia (HUSM) and Hospital Kota Bharu (HKB). The study was carried out in two phases. In phase one, a cross sectional study was conducted on 344 Malays, multiparty antenatal mothers who attended selected Maternal and Child Health Clinics (MCHC) in Kota Bharu district, from November 2003 to February 2004. Subjects were selected using two-stage sampling. Data were obtained using an interviewer guided, validated and piloted questionnaire. In order to ensure high quality of the interview, only one dedicated interviewer was involved. The questionnaire consists of a few domains namely socio-economic, accessibility, convenience, previous delivery experience, and interpersonal relationship with doctors and nurses, comfort of the patients and their relatives. The data were analyzed using logistic regression. Focus Group Discussions (FGD) were carried out in phase two in March 2004. FGD was carried out purposely to explore in depth the influencing factors, which cannot be explored through questionnaire. To fulfill this objective, 24 volunteered antenatal mothers were recruited in this phase after being consented and agreed to involve in this study. Four FGD sessions, each group consisted of six participants were conducted. Their responses were transcribed and analyzed based on the framework questions directed to them. The prevalence for choosing HUSM for delivery center was 38.0% and HKB 62.0°/o respectively. Based on the simple logistic regression, ten predictors variables namely health center, previous delivery hospital, distance to hospital, accessibility to hospital, good nursing care, short waiting hours, clean wards, children friendly (accept visitor under twelve) and fast admission to wads were significantly associated with the outcomes,. Among these only three factors remained significantly influenced when analyzed through multiple logistic regression. The final model was tested and it was found fit. The factors derived from the final model were previous delivery hospital, accessibility and children-friendly hospital. The findings in FGD support the model above and were able to extract the underlying facts. This study concludes previous delivery hospital; accessibility and children friendly hospital (hospital allows children under 12 years to visit their mothers in the wards) significantly influences the choice of hospital for delivery among antenatal mothers in Kota Bhe-ru district